Dampak Keberadaan PT. MIFA Bersaudara Terhadap Pembangan Gampong Reudeup Kec. Meureubo, Kab. Aceh Barat - Ilhamsyah (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2024)
The existence of companies that have economic potential needs to be managed so that they can be utilized optimally and are useful in improving people's standard of living. The existence of the company is an effort by the government to exploit the region's regional potential. This research examines the impact of the existence of PT. Mifa Bersaudara on the development of Reudeup village, Meureubo District, West Aceh Regency, and what activities are carried out by PT. Mifa Bersaudara who are beneficial to society. The type of research is descriptive qualitative research. Based on the results of this research, it is concluded that the impact of the existence of PT. Mifa Bersaudara towards the development of Reudeup village, Meureubo District, West Aceh Regency seen from the activities carried out by PT. Mifa Bersaudara, in the process of extracting coal mining materials, raises views or perceptions from the people of Reudeup Village, because what the company implements can have an impact on the community, both positive and negative. Activities carried out by PT. Mifa Brothers which is beneficial to society is seen from PT. Mifa Bersaudara, has carried out activities that are beneficial to the community, including activities to support orphans, donations to villages, preserving the environment around the mine by planting 1000 trees and training programs for village officials in carrying out village government activities.